Neupravičena obogatitev v večosebnih razmerjih - Lutman, Karmen (Pravni letopis, 2019)
The paper deals with the issue of invalid transfers of assets in multi-party relationships - the relationships involving (directly or indirectly) more than two persons. In cases of such transfers the issue arises, who is the recipient that has been unjustly enriched at the claimant`s expense. First, the party immediately enriched at the claimant`s expense shall be identified and second, it shall be examined whether it is possible to sue party remotely enriched at his expense. The author gives an overview of dilemmas posed by searching for a right claimant and defendant in multi-party enrichment cases and proposes solutions for typical instances of such relationships, such as assignment of claim, transfer order, contract in favour
Keywords: accession to debt; asignacija; assignment of claim; cesija; contract in favour of third party; performance-based enrichment claim; poroštvo; premoženje; stvarno pravo; suretyship; takeover of debt; takeover of performance; transfer order; unjustified enrichment